Strategi Guru Sejarah Islam Dalam Mengajarkan Kitab Khulāshah Nūr Al-Yaqīn Pada Santri Kelas 2 Mts Di Dayah Modern Darul Ulum - Safrijal Fuadi (Tadabbur: Jurnal Peradaban Islam, 2021)
This study discusses the Strategy of Islamic History Teachers in Teaching the Book of Khulāshah Nūr al-Yaqīn to Class 2 MTs Students at Darul Ulum Banda Aceh and Darul Ihsan Krueng Kalee Aceh Besar, specifically related to the learning strategies as well as the advantages and disadvantages of learning strategies applied by teachers in Islamic history subject. The focus of the research was carried out in Dayah Darul Ulum Banda Aceh and Darul Ihsan Aceh Besar. In which there are different abilities between the students of the two dayahs in understanding Islamic history subject even though they use one particular same book. The purpose of this study was to determine the learning strategies of Islamic history that applied by teachers and also to find out it’s advantages and disadvantages. This study conducted a literature review to find out concepts and theories related to the problem under study, followed by direct research to obtain concrete data in the field using qualitative descriptive research. The results showed that the strategy of Islamic history teachers in Darul Ulum Banda Aceh and Darul Ihsan Krueng Kalee Aceh Besar was in accordance with the standards of the curriculum demands, namely by using the expository learning strategy and inquiry learning strategy. Conducted through class organization, discipline of students in the classroom, the application of innovative learning methods, and effective learning media to foster student interest in studying Islamic history subject. The strategy of learning Islamic history at Darul Ulum Banda Aceh and Darul Ihsan Krueng Kalee Aceh Besar, of course, has experienced several obstacles such as limited learning time, limited media, and so on. However, it is common in a strategy implemented by teachers in any school. Even so, it would be better for a teacher to be able to minimize the shortcomings of the strategies that he applies to simplify the learning process in the classroom.